Reinterpretation of the Meaning of Qaulan Karĭman: : An Analysis of Q.S. Al-Isra’ (17): 23 Using the Maʿna cum Maghzā Approach - Awalia, Dina; Masruroh, Umi; Jainah; Valentino Saputra, Muhammad; Rusdeana; Sa’adah, Nismah; Dasuki, Akhmad (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2026)
The development of digital communication technology has transformed interactions between children and parents, raising the question of how Islamic ethical principles, particularly the concept of qaulan karĭman can be reinterpreted and applied in the context of digital communication. This study examines the meaning of qaulan karĭman in QS. Al-Isra' verse 23 using the maʿna cum maghzā approach, emphasizing understanding of the verse based on its historical meaning (maʿna) and its moral and social significance (maghzā). A qualitative hermeneutic method was employed, with primary data from the Qur'an and classical and contemporary tafsir, and secondary data from literature on digital communication and family ethics. The analysis reveals that qaulan karĭman refers not only to gentle, polite, and respectful speech but also to moral and social objectives, including maintaining parents' dignity, honor, and emotional well-being. The findings indicate that these principles can be applied in digital communication through text messages, chats, or social media, with attention to word choice, timing, emotional expression, and supportive messages. Challenges in digital communication, such as tonal misinterpretation without verbal cues, risks of conflict from delayed messages, and cultural gaps between generations are also discussed. In conclusion, the reinterpretation of qaulan karĭman provides a framework for ethical, harmonious, and empathetic digital communication, affirming that qur’anic values remain relevant and applicable in modern contexts.